2018
DOI: 10.1016/j.fertnstert.2018.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst development rate influences implantation and live birth rates of similarly graded euploid blastocysts

Abstract: In addition to aneuploidy assessment, the speed of embryo development to the blastocyst stage and an evaluation of blastocyst morphology are critical to selecting the best embryo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 44 publications
7
49
0
Order By: Relevance
“…The final inclusion was 13 studies that met the selection criteria for our meta‐analysis. Hence, 23 studies were included in the following meta‐analyses . The main characteristics and assessment for risk of bias of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The final inclusion was 13 studies that met the selection criteria for our meta‐analysis. Hence, 23 studies were included in the following meta‐analyses . The main characteristics and assessment for risk of bias of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Although all studies have reported the pregnancy outcomes following transfer of frozen‐thawed blastocysts that had developed to blastocyst stage on day 5 or day 6, studies included in present meta‐analysis varied in terms of the number of embryo transferred and the chromosomal status of blastocysts. Only three studies transfer euploid blastocysts . Five studies only transfer one embryo per cycle, while remaining studies transfer no more than two blastocysts or more than two blastocysts per cycle .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, trophectoderm and ICM morphologic grades are likely to be effective supplementary parameters to consider during embryo selection [8] . Moreover, in a study by Mohamad evaluating the role of blastocyst development rate in euploid embryo selection, day 5 euploid blastocysts had higher implantation rates and live birth rates compared with similarly graded day 6 blastocysts [9] .…”
Section: Objectivementioning
confidence: 99%